Understanding the drivers of voluntary turnover and its effect on employee performance: A literature review. - Saad, Abidah; Ishak, Suhaida; Mahmood, Nor Asiah; Abdul Aziz, Muhammad Ridzuan; Zamhury, NurulAin; Ahmad, Kartina (Journal of Islamic, Social, Economics and Development, 2025)
This literature review examines the multifaceted impact of voluntary turnover on employee and organizational performance. Voluntary turnover, often driven by factors such as job dissatisfaction, inadequate growth opportunities, and external job offers, can significantly disrupt both individual productivity and overall team dynamics. Key findings reveal that voluntary turnover not only leads to immediate costs, including recruitment and training, but also to long-term effects such as decreased morale, loss of organizational knowledge, and weakened social capital within teams. The review highlights various models explaining turnover intention and its cascading effects on performance metrics, emphasizing the need for strategic interventions. Effective retention strategies such as competitive compensation, career development programs, and supportive leadership are essential for mitigating the adverse effects of turnover. The study calls for further empirical research to explore sector-specific turnover impacts and refine approaches that enhance employee engagement and organizational resilience.